2012
DOI: 10.1093/carcin/bgs016
|View full text |Cite
|
Sign up to set email alerts
|

Control of stability of cyclin D1 by quinone reductase 2 in CWR22Rv1 prostate cancer cells

Abstract: Aberrant expression of cyclin D1, frequently observed in human malignant disorders, has been linked to the control of G(1)→S cell cycle phase transition and development and progression in carcinogenesis. Cyclin D1 level changes are partially controlled by GSK-3β-dependent phosphorylation at threonine-286 (Thr286), which targets cyclin D1 for ubiquitination and proteolytic degradation. In our continuing studies on the mechanism of prostate cancer prevention by resveratrol, focusing on the role of its recently d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 35 publications
4
42
0
Order By: Relevance
“…Furthermore, expression of p27, which has previously been described as a miR-221 target [20], [21] and as a Akt pathway downstream gene [31], was reduced after miR-221 over-expression in our model system (Figure 5B, row6). However, expression of p57, which was previously identified as a functional target of miR-221 [46], showed little change with miR-221 overexpression and downexpression (Figure 5B, row7). These results further indicate that the PTEN/Akt pathway is a major target of miR-221 and largely mediates miR-221 function.…”
Section: Resultsmentioning
confidence: 85%
“…Furthermore, expression of p27, which has previously been described as a miR-221 target [20], [21] and as a Akt pathway downstream gene [31], was reduced after miR-221 over-expression in our model system (Figure 5B, row6). However, expression of p57, which was previously identified as a functional target of miR-221 [46], showed little change with miR-221 overexpression and downexpression (Figure 5B, row7). These results further indicate that the PTEN/Akt pathway is a major target of miR-221 and largely mediates miR-221 function.…”
Section: Resultsmentioning
confidence: 85%
“…Based on our observation that NQO2 attenuates AKT activity [19], we hypothesize that resveratrol, alone or in complex with NQO2, may serve as a novel modulator of endogenous AKT by fine tuning the control of AKT activation, activity and function. This hypothesis was evaluated using the UCSF’s DOCK6.3 approach.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous studies we found that NQO2 is involved in GSK-3β-mediated cyclin D1 degradation as well as in control of AKT activity [19]. In the current study, we have expanded these studies using leads revealed by computer modeling analysis.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations